Relationship of emotional intelligence and academic performance among University of the Philippines Manila College of Dentistry Students - Abucejo, Joanna Lucille S.
INTRODUCTION: Emotional Intelligence (EI) was defined by Salovey and Mayer as the ?ability to monitor one's own and others' feelings and emotions, to discriminate among them and to use this information to guide one's thinking and actions? (Salovey, Brackett, Mayer, 2004). Many studies have correlated EI with Academic Performance and one of these is by Farooq in 2003 which says that the achievement of good academic results is contributed not only by higher intelligence but by EI as well.